Measurement of Warehouse Layout at Rice Refinery Using Shared Storage Method - Defi Irwansyah; Cut Ita Erliana; Fredy Fariska Fahrudin; Muhammad Alfian (International Journal of Engineering, Science and Information Technology, 2022)
PT. Kilang Padi Mutiara Refinery is a company engaged in rice production that produces rice, groats, and bran. The main product of this factory is rice. It can be seen in storage warehouse activities that they still experience problems with poor product placement due to irregular distances between placement and delivery areas caused by the preparation of products that are not based on inventory so that the products in the warehouse become narrower and seem messy, this triggers the accumulation of excess products. to damage the finished product packaging. Based on the existing problems, in this study, planning for layout improvements using the shared storage method was carried out to increase the effectiveness of the distance between doors to the storage area and better product placement. the steps of re-planning using the shared storage method begin by knowing the warehouse area, warehouse capacity, and other warehouse data, as well as collecting data by determining space requirements, determining space allowances, and the distance of the entrance to the storage area. From the data processing, the distance becomes more regular and can be known every distance. Based on the comparison of the initial layout and the proposal, it is known that the distance in the initial layout is 719.56 meters, while for the proposed layout using the shared storage method, the results are 593.33 meters with 13 product areas, with this loading and unloading activities become better and more effective.